2004
DOI: 10.1007/s00431-003-1376-7
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of childhood obesity management depends highly upon patient compliance

Abstract: there is an urgent need for efficient strategies to improve adherence of outpatients to obesity treatment since, in terms of reduction in body mass index standard deviation score, a beneficial outcome can be achieved for compliant obese children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 19 publications
9
54
2
2
Order By: Relevance
“…First, compared with intervention studies based on dietary restrictions, drugs, and/or lifestyle modifications, our study was relatively small; however, it should be recalled that morbid obesity represents ϳ5% of all cases of obesity (39). Second, even though the rate of dropouts was low in this study, obesity studies are usually affected by high rates of dropouts, whether they are diet (40) or surgery (23) studies. Third, this was an observational study, not a randomized clinical trial, but we have no reason to suspect that the large differences between the groups were the result of confounding factors.…”
Section: Clinical and Metabolic Outcomesmentioning
confidence: 96%
“…First, compared with intervention studies based on dietary restrictions, drugs, and/or lifestyle modifications, our study was relatively small; however, it should be recalled that morbid obesity represents ϳ5% of all cases of obesity (39). Second, even though the rate of dropouts was low in this study, obesity studies are usually affected by high rates of dropouts, whether they are diet (40) or surgery (23) studies. Third, this was an observational study, not a randomized clinical trial, but we have no reason to suspect that the large differences between the groups were the result of confounding factors.…”
Section: Clinical and Metabolic Outcomesmentioning
confidence: 96%
“…However, it has been suggested that the type, intensity, and duration of exercise of lifestyle intervention programs to promote weight loss in obese youth should be based on producing an acceptable adherence to exercise programs. (13,18) The duration of the interventions of the included studies ranged from three months to one year.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant reduction since high levels of soda consumption can be the main source of simple sugars in the diet, bringing with it a consequent caloric impact. 36 Compliance with childhood obesity management proposals is poor, 37 constituting one of the greatest obstacles to treatment. 38 This fact was also observed in the current study.…”
Section: Discussionmentioning
confidence: 99%